A focus on inflammation as a major risk factor for atherosclerotic cardiovascular diseases. (3rd March 2016) - Gregersen, Ida; Holm, Sverre; Dahl, Tuva B; Halvorsen, Bente; Aukrust, Pål
ABSTRACT: Atherosclerosis is a dynamic, pathogenic process in the artery wall, with potential adverse outcome for the host. Acute events such as myocardial infarction and ischemic stroke often result from rupture of unstable atherosclerotic lesions. Understanding the underlying pathology of such lesions and why and when they rupture, is therefore of great interest for the development of new diagnostics and treatment. Inflammation is one of the key drivers of atherosclerotic plaque development and the interplay between inflammation and lipids constitutes the hallmark of atherosclerotic disease. This review summarizes the role of inflammation in atherosclerosis and presents some of the latest discoveries as well as unmet needs regarding the role of inflammation as major risk factor in atherosclerotic disease.